2015
DOI: 10.1111/nph.13555
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in pollinator‐mediated selection on phenology, floral display and spur length in the orchidGymnadenia conopsea

Abstract: SummarySpatial variation in plant-pollinator interactions may cause variation in pollinator-mediated selection on floral traits, but to establish this link conclusively experimental studies are needed.We quantified pollinator-mediated selection on flowering phenology and morphology in four populations of the fragrant orchid Gymnadenia conopsea, and compared selection mediated by diurnal and nocturnal pollinators in two of the populations.Variation in pollinator-mediated selection explained most of the among-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
92
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 73 publications
8
92
1
Order By: Relevance
“…A variety of morphological traits, including the flower number, corolla size, and plant height, are related to the floral display (Chapurlat et al., 2015; Sletvold et al., 2010). We found significantly positive selection gradients for the corolla width and flower number of P. tibetica as well as marginally significant selection pressure on the stalk height (Table 3 and Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of morphological traits, including the flower number, corolla size, and plant height, are related to the floral display (Chapurlat et al., 2015; Sletvold et al., 2010). We found significantly positive selection gradients for the corolla width and flower number of P. tibetica as well as marginally significant selection pressure on the stalk height (Table 3 and Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…A study of Gymnadenia conopsea by Chapurlat et al. (2015) indicated that pollinators mostly exert significantly positive selection on the traits involved in the floral display (flower number, plant height, and corolla size), but the selection gradient varied among populations. In that study, there was a population in which the pollinators exerted negative selection on the corolla size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Chapurlat et al. ). In the present experiment, the opportunity for selection is expected to increase with the severity of PL, but because the experiment was conducted in a single population, the relationship between trait expression and absolute fitness is expected to remain largely the same.…”
Section: Introductionmentioning
confidence: 99%
“…This is so because not only pollinators, but also herbivores, pathogens and abiotic factors impose selection on flowers121617. In addition, only a few studies have targeted pollinator-mediated selection in different populations to analyse divergent selection10181920. Studies that document established floral trait differences among plant populations (ecotypes) or species face similar problems in identifying the primary cause for the evolution of such variation, because floral diversification is often linked to shifts in more than one ecological factor, for example in both habitat-type and pollinators212223.…”
mentioning
confidence: 99%